Applications Of Demonstrations And Drill Methods For Music Ensemble Practise In Junior High School Student In The Social Interaction Perspective - Pangesti, Yuliana Sri; Wadiyo, Wadiyo (Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the application of demonstration and drill methods to practice music skills for junior high school students in the perspective of social interaction. This research used descriptive qualitative research methods using musicology, sociology and art education approaches. The data sources used were based on the results of interviews, observations, and documentation studies. The results of the study indicated that social interaction in learning involves teachers and students. The application of the drill method in learning music ensemble material is carried out by the teacher by presenting learning material to students through repeated exercises so that students can master the subject matter and are skilled in carrying out the exercises given as a form of effectiveness in using the drill method. In practicing musical ensemble skills, the drill method makes students more organized, thorough, and sharp in memory. Social interaction in learning involves teachers and students. These interactions include ; 1) Interaction in learning, 2) teacher-student interaction, 3) student-student interaction. Interaction in learning occurs in the learning process.Teacher-student interaction occurs when students communicate with teachers. Interaction of students with students in groups of students when working on group assignments